THE INFLUENCE OF WORK MOTIVATION AND EMPOWERMENT ON PERFORMANCE WITH THE MEDIATION OF ORGANIZATIONAL COMMITMENT (STUDY AT PT. CORIN MULIA GEMILANG CENTRAL JAVA) - Fajar Herlangga; Endang Tjahjaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2026)
PT. Corin Mulia Gemilang is a national-scale company specializing in the assembly and production of agricultural tools and machinery, with a branch in Central Java. As a growing entity, it focuses on enhancing human resource quality to achieve optimal performance. This study examines the influence of work motivation and empowerment on employee performance at the Central Java branch, with organizational commitment as a mediating variable. The method used in this study was a quantitative descriptive method with primary and secondary data collection techniques through questionnaires and literature reviews. Data analysis included validity and reliability tests, coefficient of determination, F-tests, hypothesis tests, mediation tests, and Sobel tests. Findings reveal that work motivation does not significantly impact organizational commitment, whereas empowerment positively and significantly does, with stronger empowerment leading to higher commitment. Work motivation, empowerment, and organizational commitment all positively and significantly affect performance; higher levels of these factors elevate employee performance. Organizational commitment mediates the effects of both work motivation and empowerment on performance, with empowerment proving more effective through this mediation.